Relevansi Pemikiran Etika Politik Islam Al-Mawardi Terkait Kepemimpinan dalam Era Kontemporer - Andi Alya Nabilah; Gusnata Gusnata; Kurniati Kurniati (CV. Lenggogeni Data Publishing, 2024)
This research discusses the relevance of Islamic political concepts by Al-Mawardi, particularly concerning the relationship between religion and state, as expounded in his commentary